Anaemia among school children of different socioeconomical status in a city of Southern Brazil - Karini da Rosa; Luana Beatriz Limberger; Maiara de Queiroz Fischer; Caroline dos Santos; Cézane Priscila Reuter; Charise Dallazem Bertol; Jorge André Horta; Silvia Isabel Rech Franke; Daniel Prá (Taylor & Francis Group, 2024)
AbstractBackground: Iron deficiency is one of the leading causes of anaemia, with those most affected being children and women of childbearing age, in Brazil there is a scarcity of studies involving the local prevalence of anaemia. Aim: To evaluate anaemia and associated factors in schoolchildren in Santa Cruz do Sul through the analysis of biochemical and haematological markers and parasitological examination of faeces. Subjects and methods: School children from 10 to 12 years of age were evaluated through complete blood count, serum ferritin, C-reactive protein and stool parasitological examination, as well as socio-demographic characteristics and prophylaxis with ferrous sulphate in childhood. Results: It was found that 13.0% of the population was anaemic, girls were very slightly overrepresented among the anaemic children. Only 5.3% had altered haematocrit levels; 26.6% had low Mean Corpuscular Volume levels; 18.4% had low ferritin levels; 2.4% had increased C-reactive protein levels, and 21.7% had altered eosinophils. As for the socioeconomic level, classes A2 and D presented lower haemoglobin levels, as well as class D presenting lower ferritin levels, although without statistical significance. Only 6.0% of the population presented iron-deficiency anaemia and 46.0% of the schoolchildren had used ferrous sulphate supplementation in childhood. Conclusion: The prevalence of anaemia in the studied municipality is low, probably due to the high municipal human development index. Epidemiological studies are essential to characterise the population in a systematic form, to prevent future problems.